The Effect of Liquid Smoke Concentration of Tabah Bamboo (Gigantochloa nigrociliata BUSE-KURZ) on Smoke Catfish (Clarias Sp) Characteristics - Andika, I Ketut Agus Sandi; Kencana, Pande Ketut Diah; Gunadnya, Ida Bagus Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Catfish is a health food that contains good nutritional value. It is therefore important to find methods to conserve these fish to increase their consumption. Liquid smoke of stoic bamboo stems can be used as a method for making catfish processed products. The purpose of this study was to determine the effect of cooking concentration and temperature on the characteristics of smoked catfish in a bamboo stick liquid smoke solution. And also to find out the best concentration and temperature for the best organoleptic quality of smoked catfish dissolved in a stoic bamboo liquid smoke solution. The method of this research is to use a factorial completely randomized design with two factors. The first factor is the concentration of liquid smoke, namely from 1%, 2%, and 3%. The second is cooking temperature, which is from 60oC, 80oC, and 100oC. The best combination is bamboo concentration of 3% and a heating temperature of 100oC, heating is done in 4 hours and produces a pH value of 5.61, a moisture content of 56.78%, an ash content of 2.17%, a protein content of 13.46%, a fat content 5.55%, Color 4.67 (golden brown), Aroma 4.80 (aroma enough) Taste 4.93 (testeful), Texture 4.53 (solid).